Exploring the wonders of Gaharu / Noorshashillawati Azura Mohammad, Ibrahim Mohd Sobki and Yusharina Yusof - Mohammad, Noorshashillawati Azura; Mohd Sobki, Ibrahim; Yusof, Yusharina (2016)
Gaharu (agar wood, aloeswood, eaglewood, jinkoh, chen-xiang and aquilaria) have always been known as a highly valuable and one of the most expensive woods in the world. As one of the threatened plants in the world there is a dire need to preserve it due to its usefulness. This paper will explore the uses of gaharu especially from the Islamic perspective and its potential use in our daily life. Gaharu or 'Oud' as it is known in Arab countries is widely use in Islamic healing methods since the time of the Prophet Muhammad SAW. Other than medical and health products, this wonderful resource can be found in the production of food and drinks, aromatherapy, beauty and decorative items. In view of its long tradition of importance in the life of a Muslim, relevant authorities in the Muslim world should play their part in preserving this endangered resource.